Pengaruh Modal Kerja Terhadap Tingkat Likuiditas Dan Profitabilitas (Studi Kasus pada PT Timah, Tbk. dan PT Antam, Tbk.) - Supriadi, Yoyon; Fazriani, Fani (Jurnal Ilmiah Ranggagading (JIR), 2011)
This research is concerning companyâs working capital measured by financial ratio and working capital turnover that was occuring during the period of five years, that is during 2004 â 2087. The writers did this research to find out more about how the condition of working capital rotation at PT Timah Tbk. And PT Antam Tbk. The instrument used by the writers is ratio of working capital with its indicators: liquidity and profitability. Based on the result of calculation, working capital rotation at the two companies can be found out through the acquisition ratio variable, although the companyâs average cost increases year after year. Itâs influenced by the acquisition of each post at the ratio. The result shows that the condition of working capital at PT Timah Tbk. as measured by the regression test has effect of 98,6% of the companyâs liquidity. The rest, 1,4%, was influenced by other factors. And the condition of working capital at PT Antam Tbk., measured by the regression test, has effect of 96% of the companyâs liquidity. The remaining, 4%, was influenced by other factors. Itâs not so with the profitability of the two companies. From both, the working capital condition at PT Timah Tbk. measured by regression test has influence 67,1% to the companyâs liquidity, as measured by the indicators of the remaining 32,9%. And the working capital condition at PT Antam Tbk. measured by regression test has influence as high as 37,8% of the companyâs liquidity, as measured by the indicators of the larger remaining 62â% influenced by other factors.